2001
DOI: 10.1073/pnas.171311298
|View full text |Cite
|
Sign up to set email alerts
|

Human hepatitis C virus NS5A protein alters intracellular calcium levels, induces oxidative stress, and activates STAT-3 and NF-κB

Abstract: The nonstructural protein 5A (NS5A) encoded by the human hepatitis C virus RNA genome is shown here to induce the activation of NF-B and STAT-3 transcription factors from its cytoplasmic residence via oxidative stress. NS5A causes the disturbance of intracellular calcium. Ca 2؉ signaling triggers the elevation of reactive oxygen species in mitochondria, leading to the translocation of NF-B and STAT-3 into the nucleus. Evidence is presented for the constitutive activation of STAT-3 by NS5A. In the presence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
476
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 552 publications
(505 citation statements)
references
References 44 publications
18
476
1
3
Order By: Relevance
“…Host antioxidant defenses, such as GSH, catalase, MnSOD, and heme oxygenase-1, are augmented, suggesting adaptation to ROS/RNS stress [92,104,105].…”
Section: Viral Hepatitis and Free Radicalsmentioning
confidence: 99%
“…Host antioxidant defenses, such as GSH, catalase, MnSOD, and heme oxygenase-1, are augmented, suggesting adaptation to ROS/RNS stress [92,104,105].…”
Section: Viral Hepatitis and Free Radicalsmentioning
confidence: 99%
“…HCV infection is associated with increases in various markers of oxidative stress in patients [10][11][12][13]. In addition to chronic inflammation, iron overload and some of HCV proteins may help increase the oxidative burden [10,[14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this study, we tested whether ROS rapidly suppressed the activity HCV replication complex through redox signaling, to understand the biological consequence of increased oxidative stress in hepatitis C. The effect of H 2 O 2 on HCV RNA replication is also compared with that of interferon gamma (IFNγ). Interestingly, various HCV proteins have been suggested to modulate calcium metabolism [17,23,24]. HCV p7 protein may act as a calcium channel [24].…”
Section: Introductionmentioning
confidence: 99%
“…The responsiveness of IFN to HCV was expected to reflect the ability of HCV NS5a to activate NFkB, 7 which in turn would upregulate HIVLTR as a promoter. 8 We did not directly address the mechanism of HCV activation of NFkB, but we found that mutating NFkB binding sites in the HIVLTR eliminated HCV responsiveness in IFN production and secretion.…”
Section: Discussionmentioning
confidence: 99%
“…For gene delivery to the liver, rSV40 vectors have been shown to deliver enduring transgene expression to very high percentages of unselected hepatocytes, whether resting or dividing, in vitro or in vivo. 5,6 The goal of rendering transgene expression responsive to the presence of the offending HCV virus was approached by exploiting the reported ability of the HCV gene product NS5a to activate the cellular transcription factor NFkB, 7 as well as the known responsiveness of the promoter activity of the HIV-1 long terminal repeat (LTR) to NFkB. 8 Accordingly, we engineered rSV40 vectors to carry the HIVLTR as a promoter, to drive expression of murine and human IFNa and IFNg as transgenes.…”
Section: Introductionmentioning
confidence: 99%